Farmyard manure use and adoption of agricultural mechanization among smallholders in the Mahottari District, Nepal. (March 2022) - Chaudhary, Ashok Kumar; Pandit, Ram; Burton, Michael
Highlights: This research focuses on the determinants of combined use of farmyard manure and adoption of agricultural mechanization among smallholders in Nepal. Bivariate, Tobit, and Poisson regression models were used to assess likely determinants of farmyard manure use and adoption of agricultural mechanization. Increase in livestock population increases the likelihood of farmyard manure use and decreases the adoption of agricultural mechanization on farms. Adoption of agricultural mechanization is contingent on gender and age of the household head.